Foundation Treatment, Reinforcement and Design Optimization for Oil Storage Tanks at TAZAMA Pipelines Limited (Ndola, Copperbelt Province, Zambia) - Lupunga, Mwansa Andrew; Huang, Liang; Li, Haotian (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Addressing foundation soil consolidation and subsoil treatment/reinforcement pertaining to oil storage tanks is essential for ensuring their long-term structural stability and minimizing risks associated with ground movement. This study will specifically revolve around investigating Foundation Treatment, Reinforcement and Design Optimization for Oil Storage Tanks at TAZAMA Pipelines Limited Ndola Site, (a key player in the transportation of petroleum products between Zambia and Tanzania). Key content of article: - Through systematic analysis of survey data of the target area, the engineering characteristics and distribution patterns of soft soil foundations in site area was analysed and appropriate foundation treatment and reinforcement methods of oil storage tanks within the area was taken into consideration. - Demonstrated significance of applying chosen method of optimization to address the soil consolidation issues; i.e. presented through level for level analysis of application model. - Considered a 50,000m3 floating roof oil storage tank foundation for soil consolidation optimization, analysing practicality and feasibility of study. The main author of this article served as a Civil Engineering Intern at TAZAMA Pipelines Limited.